Strategi Penanggulangan Bullying Pada Sekolah Menengah Pertama Dalam Perspektif Collaborative Governance : Studi Pada SMP Islam Tikung - Zahrotul Arofah; Muhammad Roisul Basyar; Anggraeny Puspaningtyas (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The purpose of this research is to analyze the problem of bullying because it is an alarming social phenomenon that spans various environments, from schools to cyberspace. It involves repeated aggressive and detrimental actions against individuals or groups, with the aim of harming, dictating, or intimidating. Bullying has a serious impact on the victim's physical and mental well-being, including anxiety, depression, and social isolation. To overcome this problem, education and awareness about bullying are important, while involving commitment and cooperation from all parties, including schools, parents, students and the community. With collective efforts, we can create a safer and more supportive environment, and reduce incidents of bullying in society. Combating bullying is also an important effort in creating a safe and supportive environment for all individuals. Bullying prevention strategies involve a comprehensive approach, including aspects of education, awareness and involvement of all stakeholders. In this case, it is important to define bullying, identify the signs, and involve schools, parents, students and the community in overcoming this problem.